PROCESSING MEDICAL IMAGES (2019)
The invention discloses an apparatus for processing a medical image associated with a subject. The apparatus comprises a clinical information extractor for determining clinical information associated with the medical image; a plurality of image processors, each image processor for performing at least one image processing task in respect of the medical image; and an image processing manager for determining, based at least on the determined clinical information associated with the medical image, at least one image processor of the plurality of image processors to perform one or more tasks in respect of the medical image.